Evaluation of balance, functionality and quality of life in institutionalized, community and household elderly in the city of Erechim (Research, Society and Development, 2021)
Objective: To assess and correlate balance, functionality and quality of life in institutionalized, community and domiciled elderly people in the city of Erechim. Methods: The following tests were applied: To assess cognitive status, the Mini Mental State Examination was used; to assess body balance, the Berg Balance Scale and the Timed up and go test were used; the Barthel Index used to assess functionality and to assess quality of life, the instrument used was the WHOQOL-BREF. Data analysis was collected through descriptive and inferential statistics and the data represented through graphs and tables with mean and percentage. Analysis of variance (ANOVA) was applied, with p≤ 0.05 and the non-parametric Spearman correlation and Pearson correlation tests for the groups, considering p